Genome-wide identification, evolution, and transcript profiling of Aldehyde dehydrogenase superfamily in potato during development stages and stress conditions - Md. Sifatul Islam (Nature Portfolio, 2021)
Abstract The Aldehyde dehydrogenase (ALDH) superfamily comprises a group of enzymes involved in the scavenging of toxic aldehyde molecules by converting them into their corresponding non-toxic carboxylic acids. A genome-wide study in potato identified a total of 22 ALDH genes grouped into ten families that are presented unevenly throughout all the 12 chromosomes. Based on the evolutionary analysis of ALDH proteins from different plant species, ALDH2 and ALDH3 were found to be the most abundant families in the plant, while ALDH18 was found to be the most distantly related one. Gene expression analysis revealed that the expression of StALDH genes is highly tissue-specific and divergent in various abiotic, biotic, and hormonal treatments. Structural modelling and functional analysis of selected StALDH members revealed conservancy in their secondary structures and cofactor binding sites. Taken together, our findings provide comprehensive information on the ALDH gene family in potato that will help in developing a framework for further functional studies.